2021
DOI: 10.1101/2021.08.11.455966
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rab11 endosomes coordinate centrosome number and movement following mitotic exit

Abstract: The last stage of cell division involves two daughter cells remaining interconnected by a cytokinetic bridge that is cleaved in a process called abscission. During pre-abscission, we identified that the centrosome moves in a Rab11-dependent manner towards the cytokinetic bridge in human cells grown in culture and in an in vivo vertebrate model, Danio rerio (zebrafish). Rab11-endosomes are dynamically organized in a Rab11-GTP dependent manner at the centrosome during pre-abscission and this organization is requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…41 ). The ability of recycling, Rab11-positive endosomes to associate with γ-TuRC is conserved in vertebrate cells, where these endosomes contribute to spindle formation and pericentrin accumulation at the centrosome 67,68 .…”
Section: Condensatesmentioning
confidence: 99%
“…41 ). The ability of recycling, Rab11-positive endosomes to associate with γ-TuRC is conserved in vertebrate cells, where these endosomes contribute to spindle formation and pericentrin accumulation at the centrosome 67,68 .…”
Section: Condensatesmentioning
confidence: 99%
“…In human cells, centrosomes have been observed to be motile at the end of mitosis, when the centrosomes reorient themselves towards the midbody (Piel et al, 2001). Interestingly, recent work has demonstrated that this centrosome motility involves the rab11 dependent localization of PCNT to the centrosomes (Krishnan et al, 2021). It is unclear whether Kinesin-1 is involved in this process, but Kinesin does localize to centrosomes (Neighbors et al, 1988) and interacts with PCNT (Figure S4).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, despite the importance of basal body positioning at the cell cortex, little is known about how they reach their destination (Dawe et al, 2006). Centrioles have also been observed to be highly motile prior to cytokinesis, with a proposed function at the midbody to regulate abscission (Piel et al, 2001;Krishnan et al, 2021).…”
Section: Introductionmentioning
confidence: 99%